Critical gas velocity of hydrophobic ceramic membrane contactors for SO2 absorption. (15th February 2021) - Kong, Xiangli; Xu, Peng; Fu, Kaiyun; Gong, Dawei; Chen, Xianfu; Qiu, Minghui; Fan, Yiqun
Graphical abstract: Critical gas velocity of hydrophobic ceramic membrane contactors for SO2 absorption. Highlights: Membrane contactor (MC) has the maximum mass flux at critical gas velocity. A method for calculating the critical gas velocity of MC is established. Processing capacity of MC can be linearly improved by cascade design. Mass transfer of multi-tube MC was enhanced by adding baffles. Abstract: Membrane gas absorption (MGA) based on ceramic membranes is considered to be an effective technology for removing SOx from ship exhaust. To develop a convenient method for designing and amplifying a membrane contactor, the critical gas velocity was defined. Two simple connection modes, series and parallel modules, were assembled and compared with a single-tube membrane contactor. The critical gas velocity is associated with the size of the membrane element and module, based on which an empirical equation can be formulated to optimize the gas velocity in different membrane contactors. In addition, another amplifying method, using multiple tubes in one shell, was also studied with computational fluid dynamics (CFD) simulations. The results imply that the addition of baffles improves the desulfurization performance of the membrane contactor at the critical gas velocity. The methods and conclusions presented herein provide a design basis for using the contactor at an industrial scale.